Analisis Pengelolaan Dana Desa Dalam Meningkatkan Pembangunan Infrastruktur - Nurjanah, Hilda Miftakhul; Diniati, Bintis Ti'anatud; Udhma, Aulia Syafaatul; Rahmawati, Ela; Rhofiq, Mochamad (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
This researchilooks atihow villageifundsiareimanagedito improveiinfrastructure iniPulosari Village, iTulungagung Regency, from 2022itoi2024. I centeredionihowiopenithey are,ihow responsiblet hey are, and the village ifund ireport. I did ia descriptive study using iinterviews iand ilooked iat ithe 2022–2024 village ibudgets ito igather ithe idata. Results ishow Pulosari Village managesiVillageiFundsiopenly.iThey make documents available, post how they spend funds on inotice boards and theivillageiwebsite,iandiholdivillageimeetings. Theyishow accountability by Completing finance irecords thoroughly, publishing ithe ibudget ireports, iand ibeing iwatched by ithe Village Consultative iBody, isub-district iauthorities, iand facilitators. And also, ithey ihave ifull idocuments ishowing ihow the iinfrastructure projects iwent. This iincludes ipaving, irrigation, iand iretaining wall work. Overall,iPulosariivillagers hasidoneiaigreatijob managing VillageiFunds.iTheyiare transparent,iaccountable, andiresponsible, iwhich iimproves ithe village.